2008
DOI: 10.1002/dir.20103
|View full text |Cite
|
Sign up to set email alerts
|

An empirical investigation of the impact of communication timing on customer equity

Abstract: This research examines the impact of communication frequency on customer retention and spending and thus,ultimately,on a firm's Customer Equity (CE). We conduct an empirical study in the context of permissionbased e-mail marketing in the entertainment industry and find that intercommunication timing has a dramatic impact on customer behavior. Message scheduling affects both attrition and the customer response and thus has a critical impact on the value of one's customer base. The impact of intercontact duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 18 publications
(24 reference statements)
1
26
0
Order By: Relevance
“…Data by, for example, Mailchimp (Foreman, 2014) and GetResponse (Pietras, 2013) show that sending newsletters during weekday mornings yields the highest opening rates, whereas weekend days yield the lowest. Other studies have shown that the best days of the week to send an e-mail are Tuesday and Sunday (Drèze & Bonfrer, 2008); further others that the day of the week makes very little difference at all in terms of opening rates (Experience Marketing Services, 2013).…”
mentioning
confidence: 99%
“…Data by, for example, Mailchimp (Foreman, 2014) and GetResponse (Pietras, 2013) show that sending newsletters during weekday mornings yields the highest opening rates, whereas weekend days yield the lowest. Other studies have shown that the best days of the week to send an e-mail are Tuesday and Sunday (Drèze & Bonfrer, 2008); further others that the day of the week makes very little difference at all in terms of opening rates (Experience Marketing Services, 2013).…”
mentioning
confidence: 99%
“…From a methodological perspective, it complements the growing literature in marketing that highlights the usefulness of HMMs for understanding customer dynamics in a variety of marketing problems (e.g., Ascarza and Hardie 2013, Montoya et al 2010, Netzer et al 2008, Schwartz et al 2014). More broadly, our work also relates to the literature on email marketing (e.g., Bonfrer and Drèze 2009, Drèze and Bonfrer 2008, Kumar et al 2014, as email communications and newsletters are one example of hybrid settings.…”
Section: Discussionmentioning
confidence: 99%
“…(Blattberg & Deighton, 1996;Dorsch & Carlson, 1996;Hogan, Lemon, & Rust, 2002;Kumar & George, 2007;Persson & Ryals, 2010;. The basis of the customer equity is the customer's lifetime value (Drèze & Bonfrer, 2008).…”
Section: Customer Equitymentioning
confidence: 99%